2014
DOI: 10.3844/ajassp.2014.1369.1378
|View full text |Cite
|
Sign up to set email alerts
|

The High Volume Reuse of Hybrid Biomass Ash as a Primary Binder in Cementless Mortar Block

Abstract: High Calcium Wood Ash (HCWA) and Pulverised Fuel Ash (PFA) are by-products from the wood biomass and coal energy production which are produced in large quantity with combined annual production of 500 million tonnes. This poses a serious problem for disposal of the waste material especially at places where land is scarce. The prescribed study was aimed to examine the mineralogical phases and their respective amount present in the industrial wastes which governs the hydration mechanism towards self-sustained sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…Biomass ashes are usually valorised industrially as an additive in cement, in the neutralisation of acid waste streams, as raw materials in fertiliser and ceramic glazes production [20], and a recent study has shown that their addition in mortars as aggregate can also enhance the absorption of Volatile Organic Compounds (VOCs) [21]. Their alkaline nature and mineralogical content in general have motivated some research teams to investigate their role in the production of inorganic polymers, without the addition of any manufactured chemical activator, as was the case with wood and some agricultural residues [10,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass ashes are usually valorised industrially as an additive in cement, in the neutralisation of acid waste streams, as raw materials in fertiliser and ceramic glazes production [20], and a recent study has shown that their addition in mortars as aggregate can also enhance the absorption of Volatile Organic Compounds (VOCs) [21]. Their alkaline nature and mineralogical content in general have motivated some research teams to investigate their role in the production of inorganic polymers, without the addition of any manufactured chemical activator, as was the case with wood and some agricultural residues [10,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Povećanjem udjela PDB-a raste i električna provodljivost. [20] Kad je 10 % PDB-a u masi veziva, smanjuje se ukupno skupljanje (uslijed sušenja i autogeno), što rezultira manjim naprezanjima unutar elementa u konstrukciji [4].…”
Section: Svojstva Trajnosti Cementnih Kompozita S Pdb-omunclassified
“…Troškovi upravljanja otpadnim pepelom iz biomase iznose između 200 i 500 eura po toni, a u budućnosti se može očekivati povećanje troškova odlaganja u obliku poreza ili naknada na odlaganje, kao i poteškoće u pronalaženju novih odlagališta te strože EU direktive vezano uz odlaganje [13]. Zasad se 70 % pepela iz drvne biomase (PDB) odlaže, 20 % se nastoji primijeniti kao dodatak tlu u poljoprivredi i 10 % za ostale namjene [2,14]. Odlaganje pepela iz drvne biomase bez ikakva oblika kontrole može prouzročiti onečišće-nje zraka sitnim česticama nošenim vjetrom [15], onečišćenje podzemnih voda zbog izluživanja teških metala iz pepela, te ulazak teških metala u prehrambeni lanac [16].…”
Section: Gospodarenje Pepelom Iz Drvne Biomaseunclassified